CFRP composite retrofitting effect on the dynamic characteristics of arch dams - Altunisik, Ahmet Can; Gunaydin, Murat; Sevim, Baris; Bayraktar, Alemdar; Adanur, Suleyman (ELSEVIER SCI LTD, 2015)
The purpose of this study is to investigate the effect of retrofitting dynamic characteristics of a damaged laboratory arch dam model, subsequently repaired with high-strength structural mortar and strengthened with composite carbon fiber reinforced polymer. This study constructed in laboratory conditions is a prototype arch dam-reservoir-foundation model. Five test cases of ambient vibration on the arch dam model illustrate the changes in dynamic characteristics: natural frequency, mode shape, and damping ratio, before and after retrofitting. The ambient vibration tests collected data from the dam body during vibrations by natural excitations which provided small impacts and response signals from sensitivity accelerometers placed at crest points. Enhanced Frequency Domain Decomposition Method in the frequency domain extracts the experimental dynamic characteristics. At the end of the study, experimentally identified dynamic characteristics obtained from all test cases have been compared with each other. Apparently, after the retrofitting, the natural frequencies of the dam body increased considerably, demonstrating that the retrofitting, including repairing and strengthening is very effective on the flashback of initial dynamic characteristics. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Ambient vibration test; Carbon fiber reinforced polymer; Dynamic characteristics; Enhanced frequency domain decomposition; Prototype arch dam-reservoir-foundation model; Retrofitting; Strengthening; SEISMIC RESPONSE; AMBIENT; IDENTIFICATION; PERFORMANCE; BEHAVIOR; JOINTS; Engineering; Geology